PENGEMBANGAN VIDEO INTERAKTIF YANG TERINTEGRASI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Novi, Novi Aprilia Nazarmi; Maryono; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted at SDN 15/IV Kota Jambi in November 2025. The research data were obtained through validation questionnaires from experts, practitioner questionnaires, student response questionnaires, as well as interviews with teachers and students. The collected data were then analyzed to determine the feasibility of the developed interactive video. This research and development study produced an interactive video designed for fourth-grade elementary school students, developed using the DDDE (Decide, Design, Develop, and Evaluate) model. The validation results showed that the design expert gave an average score of 4.7 (very valid), the material expert gave an average score of 4.8 (very valid), the language expert gave an average score of 3.5 (very valid), and the media expert gave an average score of 4.7 (very valid). Furthermore, the teacher response questionnaire obtained an average score of 4.3 (very practical). The student response questionnaire in the small group trial gained an average score of 3.96 (very practical), while in the large group trial it reached an average score of 4.44 (very practical). Based on these findings, it can be concluded that the interactive video for fourth-grade elementary school students is highly valid, highly practical, and feasible to be used in teaching IPAS (Science and Social Studies Integration) on the topic of magnets for fourth-grade elementary school learning.